2019
DOI: 10.3389/fpsyg.2019.00203
|View full text |Cite
|
Sign up to set email alerts
|

Collective Narcissism and In-Group Satisfaction Are Associated With Different Emotional Profiles and Psychological Wellbeing

Abstract: The social identity approach to wellbeing posits that social identifications provide psychological resources that contribute to individual wellbeing. Unless individuals identify with stigmatized groups or groups whose norms prescribe damaging behaviors, identifying with groups seems beneficial. This article explores the possibility that the different ways individuals approach the same social identity (labeled collective narcissism vs. in-group satisfaction) may be differentially associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
64
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 75 publications
(113 reference statements)
10
64
2
Order By: Relevance
“…In addition, after their positive overlap was partialled out, collective narcissism was positively and in-group satisfaction was negatively associated with out-group derogation (Golec de Zavala, Cichocka, & Bilewicz, 2013a). We posit, therefore, that the 1 Confirmatory and exploratory factor analyses conducted on items measuring collective narcissism and in-group satisfaction indicate a two factorial latent structure, consistent with the claim that collective narcissism and in-group satisfaction are distinguishable and correspond to different beliefs about the in-group (Dyduch-Hazar, Mrozinski, & Golec de Zavala, 2019;Golec de Zavala, 2019). positive overlap between in-group satisfaction and collective narcissism may obscure (1) the opposite relationships those variables have with self-esteem, and (2) the indirect, negative link between self-esteem and out-group derogation via collective narcissism.…”
supporting
confidence: 57%
“…In addition, after their positive overlap was partialled out, collective narcissism was positively and in-group satisfaction was negatively associated with out-group derogation (Golec de Zavala, Cichocka, & Bilewicz, 2013a). We posit, therefore, that the 1 Confirmatory and exploratory factor analyses conducted on items measuring collective narcissism and in-group satisfaction indicate a two factorial latent structure, consistent with the claim that collective narcissism and in-group satisfaction are distinguishable and correspond to different beliefs about the in-group (Dyduch-Hazar, Mrozinski, & Golec de Zavala, 2019;Golec de Zavala, 2019). positive overlap between in-group satisfaction and collective narcissism may obscure (1) the opposite relationships those variables have with self-esteem, and (2) the indirect, negative link between self-esteem and out-group derogation via collective narcissism.…”
supporting
confidence: 57%
“…The average effect size for this association is moderate, significant (with 95% CI [0.22,0.27]), and twice as strong as the average association between collective and grandiose narcissism, and it is less heterogeneous. Analyses also confirmed that across different countries, collective narcissism was associated with low self‐esteem via vulnerable narcissism (Golec de Zavala, ). Thus, the belief that the ingroup’s exceptionality is not sufficiently recognized by others is associated with a similar belief about the self.…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 60%
“…Supporting such interpretations, research (Golec de Zavala, ) indicates that nationalism is uniquely positively associated with grandiose narcissism, while collective narcissism is uniquely negatively associated with grandiose narcissism, that is, an individual sense of agentic superiority over others. In addition, collective narcissism is uniquely related to vulnerable narcissism, that is, antagonistic self‐entitlement manifesting as resentment for the lack of individual recognition (Miller, Lynam, Hyatt, & Campbell, ).…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 99%
See 2 more Smart Citations